2015
DOI: 10.1007/s10965-014-0591-4
|View full text |Cite
|
Sign up to set email alerts
|

Compatibilization of polypropylene/recycled polyethylene terephthalate blends with maleic anhydride grafted polypropylene in the presence of diallyl phthalate

Abstract: Bi-functional co-agent, diallyl phthalate (DAP), −assisted melting free-radical grafting of maleic anhydride (MAH) on polypropylene (PP) is carried out by reactive extrusion. The PP/recycled polyethylene terephthalate (rPET) blends with and without PP-g-MAH/DAP (PP grafted with both MAH and DAP) are conducted on a twin-screw extruder. It reveals that the introduction of DAP can significantly enhance the grafting degree of MAH and decrease the chain scission of PP. The maximum extent of MAH grafting (1.5 wt.%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 49 publications
2
17
0
Order By: Relevance
“…New absorption peaks observed at 1856 and 1780 cm −1 in the FTIR spectra of the three functionalized PPs are attributed to the symmetric and asymmetric stretching vibration of the carbonyl groups (C=O) of MAH [9,11,24]. The absorption peaks observed at 1722 cm −1 in PP-g-MAH/ DAP and at 1690 cm −1 in PP-g-MAH/TAIC are assigned to the C=O of DAP and TAIC, respectively [25,26]. These results show that MAH has been successfully grafted on PP with the assistance of different co-monomers.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…New absorption peaks observed at 1856 and 1780 cm −1 in the FTIR spectra of the three functionalized PPs are attributed to the symmetric and asymmetric stretching vibration of the carbonyl groups (C=O) of MAH [9,11,24]. The absorption peaks observed at 1722 cm −1 in PP-g-MAH/ DAP and at 1690 cm −1 in PP-g-MAH/TAIC are assigned to the C=O of DAP and TAIC, respectively [25,26]. These results show that MAH has been successfully grafted on PP with the assistance of different co-monomers.…”
Section: Resultsmentioning
confidence: 92%
“…However, St has a limited ability to reduce chain scission of PP molecules, resulting in poor mechanical performance and thus the tearing of PP-g-MAH/St during the testing process. PP-g-MAH/DAP shows better T-peeling and heat-sealing strengths than PP-g-MAH/St, as shown in figure 10, which is due to the higher grafting degree of MAH and the restriction of DAP on chain scission [25]. The coordination between DAP and Ti treated Al foil surface might also contribute to the improvement of T-peeling and heat-sealing strengths [36].…”
Section: Adhesive Performancementioning
confidence: 94%
See 1 more Smart Citation
“…Compared to uncompatibilized blend due to the elastomeric nature of SEBS in SEBS‐ g ‐MAH. Zhu et al carried out a research on PP/PET (80/20 wt.) blend with polypropylene grafted maleic anhydride and diallyl phthalate(PP‐g‐MAH/DAP) as a compatibilizer and observed better size distribution, dispersion, better mechanical properties with respect to the uncompatibilized PP/recycled PET blend.…”
Section: Introductionmentioning
confidence: 99%
“…HDPE-g-MA and PP-g-MA), ethylene-propylene-diene terpolymer (EPDM-g-MA) and hydrogenated styrene-butadiene-styrene terpolymer (SEBS-g-MA) [20]. The effectiveness of PP-g-MA was previously demonstrated in blends of PS/PP [21], PP/PET [22], HDPE/PP [23] and PA12/PP [24]. Tóth et al [25] reported positive effects of maleic-anhydride grafted polyolefins (PO-g-MA) on tensile and impact properties of PE/crumb rubber system.…”
Section: Introductionmentioning
confidence: 99%